2004
DOI: 10.1002/bip.20127
|View full text |Cite
|
Sign up to set email alerts
|

The design of a potent inhibitor of the hepatitis C virus NS3 protease: BILN 2061—From the NMR tube to the clinic

Abstract: The virally encoded serine protease NS3/NS4A is essential to the life cycle of the hepatitis C virus (HCV), an important human pathogen causing chronic hepatitis, cirrhosis of the liver, and hepatocellular carcinoma. Until very recently, the design of inhibitors for the HCV NS3 protease was limited to large peptidomimetic compounds with poor pharmacokinetic properties, making drug discovery an extremely challenging endeavor. In our quest for the discovery of a small-molecule lead that could block replication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…Tsantrizos et al [101] used SAR by NMR to optimise small-molecule hepatitis C virus NS3 protease inhibitors. The observed results have shown that the binding affinity and potency were highly dependent on the ring size, the stereochemistry of each chiral centre and the electrostatic potential of the aromatic substituents.…”
Section: Ligand-protein Interactionsmentioning
confidence: 99%
“…Tsantrizos et al [101] used SAR by NMR to optimise small-molecule hepatitis C virus NS3 protease inhibitors. The observed results have shown that the binding affinity and potency were highly dependent on the ring size, the stereochemistry of each chiral centre and the electrostatic potential of the aromatic substituents.…”
Section: Ligand-protein Interactionsmentioning
confidence: 99%
“…Despite the shallow substrate binding site of the HCV NS3 serine protease, a number of inhibitors of this enzyme have been identified (17,43,55,59). Generally, these inhibitors are substrate-based peptidomimetic compounds.…”
mentioning
confidence: 99%
“…Successful examples of small-molecule inhibitors include the protease inhibitors telaprevir (VX-950) and boceprevir (SCH503034), the nucleoside polymerase inhibitor R7128, and the nonnucleoside NS5B inhibitor VCH-222. The macrocyclic inhibitor of NS3, BILN 2061, despite being suspended in clinical development, is a proof-of-principle peptidomimetic compound that was designed to mimic the conformation of substrate-based hexapeptides bound to NS3 and is active both in vitro and in vivo (18,36). In the present study, we report the development of tetracarboxyphenylporphyrins for feasible interaction with biomolecules involved in HCV replication.…”
Section: Discussionmentioning
confidence: 99%